Are SMEs large firms en miniature? Evidence from a growth analysis - Christina E. Bannier; Sabrina Metz (Frankfurt School of Finance & Management, 2010)
Based on German data between 1999 and 2007, we analyze the growth factors of SMEs and contrast them with those of large _rms. Differences show up both in balance sheet and employment growth. While we confirm earlier results on inherent growth structures and the influence of firm age, we derive several new, complex growth effects that set SMEs apart: particularly ownership type and ownership structure play a distinctive role that may additionally interact with other variables affecting growth, such as, e.g. profitability or capital structure. As such, the distinction - according to size - between SMEs and large firms may not be sufficiently meaningful unless combined with further information on ownership type and structure and, preferably, also on firm age.
Keywords: G3; L25; 330; Small and medium-sized enterprises; growth analysis; panel analysis; system GMM estimation; Klein- und Mittelunternehmen; Unternehmenswachstum; Vergleich; Großunternehmen; Panel; Schätzung; Deutschland